Effect of Screen Exposure is Linked to Weight Gain in Females - Awasthi, Shrini; Sharma, Swati (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2018)
Obesity is slowly becoming a grave health concern. There are many reasons for weight gain in different age groups some of which are – physical inactivity, improper diet, stress, hectic schedule, improper or inadequate sleep, smoking, excess intake of tea and coffee, hormonal imbalances, cardiac issues, blood pressure, blood sugar imbalances etc. One very important factor that is contributing to rise of obesity nowadays is the increased use of gadgets like television, smart phone, tablet, laptop etc.